The Influence of Social Norms and Attitude Towards Food Waste Reductions at Five-Star Hotels in Jakarta - Muljani, Borromia Faustina; Brian, Reagan; Juliana, Juliana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study investigates the influence of social norms and attitudes on the intention to reduce food waste in five-star hotels in Jakarta. A quantitative research design was employed, collecting data from 220 participants, including hotel guests, restaurant patrons, and hotel employees, through an online questionnaire. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that both social norms (β = 0.34, p < 0.001) and attitudes (β = 0.45, p < 0.001) significantly and positively affect food waste reduction intentions. The model accounts for 61.6% of the variance in behavioral intention (adjusted R²), reflecting moderate predictive power. These findings support the Theory of Planned Behavior and contribute theoretical insights into consumer behavior in the hospitality industry. From a practical perspective, the study emphasizes the need for guest-oriented educational campaigns and socially-driven communication strategies to foster a culture of food conservation. The study's limitations include the reliance on self-reported data, which may be subject to social desirability bias. Future research is encouraged to explore additional factors, such as perceived behavioral control, moral norms, and environmental awareness, to strengthen the model’s explanatory capacity and promote more comprehensive sustainable practices within the hospitality sector.